Detection and prediction of epileptic seizure using different machine learning classifiers - Crystal, Afnan Ahmed; Tasnim, Nuna; Jamal, Subha Sumaiya B; Rahman, Md. Ashikur (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.